La gestion de l’eau et l’éducation environnementale dans les documents pédagogiques au Burkina Faso - Binto Ouedraogo (VertigO)
Burkina Faso, a sahelian country like many others is face to problems of development related to serious ecological consequences: ozone deterioration, climatic changes, soil erosion, deforestation…Face to these hazards the government has taken institutional decisions for the environment protection: six national commitments have been taken which “each school, one grove”, the adoption of environment code, the adoption of a national strategy for environmental education which involved all the formal and non formal education aspects. Without adequate environment, no sustainable development is possible. In this fight for … environment, the government is assisted by international institutions like UNICEF, Non Government Organizations and associations as Helen Keller International, Amicales des Forestiers du Burkina, Green Cross…The current communication tries to provide an overview on environment education and water management according to pedagogical documents conceived in Burkina and the action of UNICEF and its partners in this sector.